Pengaruh Pola Asuh Orang Tua Terhadap Karakter dan Hasil Belajar Matematika - Suyatno, Dyah Purwaningsih; B, Bagiya; Ngazizah, Nur (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The purpose of this study was to determine how the influence of parenting patterns on the character and mathematics learning outcomes of fourth-grade students of SD Negeri 2 Puliharjo in the 2023/2024 Academic Year. This research is a quantitative study. The subjects of the study were 26 fourth-grade students of SD Negeri 2 Puliharjo in the 2023/2024 Academic Year in qualitative research, the term population, let alone sample, was not used. So the population in this study were 26 fourth-grade students of SD Negeri 2 Puliharjo and the data source used a saturated sample, namely the entire population was used as a research sample. Data were collected using questionnaires and tests. Data were analyzed using simple linear regression analysis. The results showed that parenting patterns had a significant effect on students' character with a significance value of t count of 0.000. Parenting patterns had a significant effect on students' mathematics learning outcomes with a significance value of t count of 0.000.